Genetic Bottlenecks in Isolated Populations (Zoological Archives: An International Journal, 2026)
Genetic bottlenecks -- severe reductions in population size that dramatically reduce genetic diversity through randomgenetic drift -- are among the most consequential genetic events for isolated wildlife populations, leaving lastingsignatures in genome-wide patterns of heterozygosity, linkage disequilibrium, and runs of homozygosity that persist fordozens to hundreds of generations post-bottleneck. This study quantified the genomic signatures and demographicconsequences of genetic bottlenecks across 42 isolated vertebrate populations representing 28 species (mammals: 18species; birds: 6; reptiles: 4) from European island, mountain, and fragmented mainland habitats, using whole-genomesequencing (mean 14.8x coverage; 284 individuals) and historical census data (1950-2024) to reconstruct bottlenecktiming, severity, and recovery trajectory. Bottleneck severity -- quantified as the ratio of minimum census population topre-bottleneck estimate -- ranged from 0.004 (alpine ibex Capra ibex, near-extinction at 14 individuals in 1844) to 0.48(island fox Urocyon littoralis Channel Islands). Genome-wide heterozygosity (He) was negatively correlated withbottleneck severity (r = -0.74, p < 0.001) and positively correlated with post-bottleneck recovery duration (r = +0.68, p 1.0) with 82.4% accuracy. Species with GRI > 0.60 showed significantlyhigher lambda (mean 1.084 +/- 0.024) than species with GRI < 0.40 (lambda 0.924 +/- 0.038; p < 0.001), confirminggenomic recovery as a predictor of population growth rate.